More Female Manager Hires through More Female Managers? Evidence from Germany - Mario Bossler; Alexander Mosthaf; Thorsten Schank (Institute for the Study of Labor (IZA), 2016)
This paper investigates if there is state dependence in the gender composition of managers in German establishments. We analyze whether the number of hired female managers (respectively the share of females within hired managers) depends on the past hiring decisions of an establishment. Using administrative data, we apply dynamic linear models and dynamic tobit models accounting for unobserved heterogeneity and the endogeneity of lagged dependent variables. We find that an increase of female manager hires in present leads to more female hired managers in the future. Similarly, the number of male manager hires also exhibits state dependence.
Keywords: C23; J16; J71; M12; 330; female managers; gender discrimination; state dependence; dynamic panel data models